Smoking prevalence in urban and rural populations: findings from California between 2001 and 2012. (3rd March 2016) - Liu, Lianqi; Edland, Steven; Myers, Mark G.; Hofstetter, C. Richard; Al-Delaimy, Wael K.
ABSTRACT: Background : Tobacco smoking and related health problems are still major public health concerns in the United States despite the declining smoking prevalence. Objectives : This study explored differences in smoking prevalence between urban and rural areas potentially relevant to tobacco control efforts in California. Methods : Public use adult smoking data from the California Health Interview Survey (CHIS) between 2001 and 2011–2012 were analyzed. A total of 282 931 adults were surveyed across the six CHIS cycles. A ZIP code-based geographic classification (Urban, Second-City, Suburban, and Town/Rural) was used to examine the association between smoking prevalence and area of residency. Results : The overall smoking prevalence in California decreased from 17.0% in 2001 to 13.8% in 2011–2012. Within each CHIS cycle, the Town/Rural areas had the highest smoking prevalence, followed by Urban and Second-City areas, and Suburban areas had the lowest. Pooled data from all CHIS cycles showed a similar pattern, with rates in Urban, Second-City, Suburban and Town/Rural areas being 15.2%, 15.2%, 13.1% and 17.3%, respectively. Weighted multivariate logistic regression analysis indicated significantly higher odds of smoking in Urban, Second-City and Town/Rural areas compared to Suburban areas (all adjusted odds ratios > 1.10), although this trend varied by race/ethnicity, being present in non-Hispanic Whites and not present in Hispanics. Conclusions : Town/Rural and Urban populations of California are consistently at higher risk of smoking than Suburban populations. These results indicate a need for population-specific tobacco control approaches that address the lifestyle, behavior, and education of disparate populations within the same state or region.